Effect of Moderate Intensity Combination Exercise on Reducing Inflammation in Obese Women - Amiruddin, Putri Nabila; Sugiharto (Journal of Strength and Conditioning, 2025)
High inflammation in obesity is a serious problem for improving the quality of human resources. High inflammation in obesity conditions will interfere with health metabolism, thus having an impact on the occurrence of complications in obesity. Regular physical exercise is believed to be a strategic method for individuals who are obese. The purpose of this study is to prove the combination exercise on reducing inflammation in obesity. A total of 20 obese women with a BMI of ≥25 kg/m2 were divided into 2 groups, namely the control group (K1; n = 10), the combination exercise intervention group (K2; n = 10). Exercise is done at moderate intensity (aerobic exercise 60-70% HRmax and strength training 60-70% 1-RM), on aerobic exercise for 40 minutes and strength training as many as 4-6 sets, 10-15 reps, with a frequency of 5x/week, for 4 weeks. Inflammatory levels use the biomarker IL-1β. Inflammatory levels were measured at the time of pretest and posttest using the ELIS method. The Paired Sample T-Test showed no difference in the average inflammatory level between the pretest and the posttest in K1 (22.45 ± 7.15 vs 22.72 ± 6.87 ng/mL; p= 0.867), and in K2 there was a significant difference (23.86 ± 10.18 vs 16.27 ± 3.60 ng/mL; p= 0.037). It can be concluded that with 4 weeks of moderate-intensity combination exercise, it is proven to reduce inflammation levels in obese women.